ANALISIS MANAJEMEN PENGADUAN KANAL PENGADUAN â€œSAPA MBAK ITAâ€ KECAMATAN TEMBALANG - Maya Silvia; Budi Puspo P.; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2023)
This research ia focused on the implementation of complaint management implemented by the Tembalang District Government on complaints sent by the public through the "Sapa Mbak Ita" Online Complaint Channel. Being a region that gets a very significant increase in Community Satisfaction Index (IKM) scores every year, it is interesting study to analyze the performance of service officers in handling and responding to complaints sent by the public. The purpose of this research is to analyze the strategy and implementation of complaint management in Tembalang District and to analyze the factors that support and hinder the complaint service process in Tembalang District. The research method in this study is a qualitative method with a descriptive approach, namely exploring in depth the research phenomenon to get results from existing problems. Data collection techniques in this study used purposive sampling techniques, namely to gather information from individuals or groups who have understanding and ability to research problems which are deepened by interviews, observation, documentation and literature studies. The theory used in this study is Tjiptono's 10 theories of Management Complaintâ€™s Effectiveness including: 1) simplicity, 2) speed, 3) record/feature, 4) confidential/confidential, 5) analytical skills, 6) human resources, 7) visible/socialization , 8) commitment, 9) facilities, and 10) fairness/fairness. These results indicate that Tembalang District is well committed to providing complaint services to the community, has good analytical skills with a briefing strategy to reduce communication errors, is very responsive and fast in taking action on complaints sent by the community. Inhibiting factors include the quantity of human resources that is not proportional to the number of services, socialization that has not been maximized, the completeness of features that still make it difficult for the community and facilities that have not been maximized